ANALISIS PENDAPATAN WANITA PADA AGROINDUSTRI LEPAT BUGI DI DESA PALUNG RAYA KECAMATAN TAMBANG KABUPATEN KAMPAR - Rosnita Rosnita; Evy Maharani; Reana Andam Dewi (Fakultas Pertanian, Universitas Riau, 2020)
The purpose of this research are, to analyze women income agroindustry lepat bugi. The data of this research was conduted from Agustus 2016 till Maret 2017. This research use census method, the technique sampling of this method population of lepat bugi euntreprenuer of regency Kampar taken from 20. The selection of the research site with the consideration that many agroindustri lepat bugi that are owned by women. The result of the analysis women income agroindustry lepat bugi Rp.1.707,119 and efficiency value of 1,40 which means the business is worth developing.